Going beyond Work-First and Human Capital approaches to employability: the added-value of the Capability Approach - Margherita Bussi (Social Work & Society, 2014)
Research on Active Labour Market Policies (ALMPs) has paid less attention to the quality and the extent of individualisation, which are both embedded in the concept of "employability". On the one hand, taking into account the quality of employability policies means considering the objectives of the policies themselves; on the other hand, investigating how and to what extent individualisation is actually delivered calls for a deeper analysis of the implementation process, where employability is interpreted and adapted. Grasping both aspects raises challenges dealing with the analytical approach to research on ALMPs. The paper aims at contributing to this methodological issue related to the cognitive and implementation dimensions of ALPMs by developing an analytical tool based on three ideal-types of employability. The contribution elaborates on the relevant analytical dimensions of the well-known Work-First and Human Capital approach by using the Capability Approach (CA) perspective (Nussbaum & Sen, 1993). The paper argues that the CA constitutes an added value for developing a new analytical tool for investigating employability policies because it: 1) identifies the underlying normative concept of employability against which quality can be assessed; 2) depicts the degree of individualisation actually implemented while going beyond a labour market-centred approach to ALMPs.